2006
DOI: 10.1111/j.1525-1438.2006.00536.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of uterine sarcomas: results from 14 years worth of experience in the Kinki district in Japan (1990-2003)

Abstract: To review clinical outcomes and therapeutic varieties, we were invited to submit data from the patients who were treated for uterine sarcomas in Japan from 1990 to 2003. Uterine sarcomas were defined as leiomyosarcoma (LMS), endometrial stromal sarcoma (ESS), and carcinosarcoma (CS). Of a total of 97 patients, 36 (37.1%) were diagnosed with LMS of the uterine corpus, 15 (15.5%) with ESS, 46 (47.4%) with CS. Median age at diagnosis was 59 (21-85) years. Clinical stages based on FIGO were 41 (42.3%) with stage I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
1
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 25 publications
(44 reference statements)
6
28
1
5
Order By: Relevance
“…As reported in other studies (Chavenic et al,1999;El Husseiny et al, 2002;Kokawa et al, 2006;KoivistoKorander et al, 2008;Tsikouras et al, 2008), in our study most patients were diagnosed at early stages (stage I-II, 63.4%). Most of the patients in LMS group and ESS group were diagnosed at stage I-II (74.1% and 88.9% respectively), while MMMT group was mainly diagnosed at advanced stages (stage III-IV, 64%).…”
Section: 1935 Prognostic Factors and Treatment Outcomes In Patients supporting
confidence: 70%
See 1 more Smart Citation
“…As reported in other studies (Chavenic et al,1999;El Husseiny et al, 2002;Kokawa et al, 2006;KoivistoKorander et al, 2008;Tsikouras et al, 2008), in our study most patients were diagnosed at early stages (stage I-II, 63.4%). Most of the patients in LMS group and ESS group were diagnosed at stage I-II (74.1% and 88.9% respectively), while MMMT group was mainly diagnosed at advanced stages (stage III-IV, 64%).…”
Section: 1935 Prognostic Factors and Treatment Outcomes In Patients supporting
confidence: 70%
“…There is no consensus on prognostic factors of uterine sarcomas. Several studies have found no effecet of age on survival (Peters et al,1984;El Husseiny et al, 2002;Park et al, 2008), whereas some studies reported that patients younger than age 50 years had longer survival (Nagell et al, 1986;Kokawa et al, 2006). In our study patients younger than age 60 years had significantly longer RFS and OS.…”
Section: 1935 Prognostic Factors and Treatment Outcomes In Patients supporting
confidence: 50%
“…The problem with regard to earlier studies is that the various conditions were aggregated, preventing meaningful analysis of any single variable (6)(7)(8)(9)(10)(11)(12)(13). Further, some recent studies are still using the older classification (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) …”
Section: Discussionmentioning
confidence: 99%
“…Depending on the histological classification used, uterine sarcomas represent about 3 to 9% of cancers of the corpus uteri and 1% of all cancers of the female reproductive system [19,21]. The prognosis for certain histological types, such as uterine sarcoma, is quite poor; overall 5-year survival ranges from 17 to 53% [21][22][23]. For endometrial stromal sarcoma, the www.e-shaw.org prognosis is better than for other uterine sarcomas.…”
Section: Endometrial Cancermentioning
confidence: 99%